Photobiomodulation Impact on Tooth Movement and Orthodontic Treatment - Meng, Fei (International Journal of Public Health and Medical Research, 2024)
Photobiomodulation (PBM), a therapeutic modality utilizing low-intensity light in the visible and near-infrared spectrums, has garnered significant attention in the field of dentistry, particularly in the context of orthodontic treatment. This study delves into the mechanisms by which PBM influences tooth movement, examines its efficacy in accelerating orthodontic procedures, and discusses potential clinical implications. By analyzing recent advancements and research findings, we aim to provide an in-depth understanding of PBM' s role in enhancing patient outcomes and treatment experiences.